2017
DOI: 10.1016/j.jaci.2016.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Human circulating group 2 innate lymphoid cells can express CD154 and promote IgE production

Abstract: This study provides the first evidence that human ILC2s can express CD154 and stimulate the production of IgE by B lymphocytes through IL-25/IL-33 stimulation or TLR triggering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 34 publications
2
82
0
1
Order By: Relevance
“…ILCs have been shown to regulate B cell responses in mice [102, 103] and humans [104, 105] (Fig. 1).…”
Section: Interaction With Other Cell Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…ILCs have been shown to regulate B cell responses in mice [102, 103] and humans [104, 105] (Fig. 1).…”
Section: Interaction With Other Cell Typesmentioning
confidence: 99%
“…Noteworthy, several phenotypic differences between mice and humans were described, with murine ILCs expressing APRIL and DLL1, but lacking BAFF and CD40L expression [105]. Moreover, TLR-induced CD40L expression has been recently demonstrated in circulating human ILC2, resulting in these cells gaining the potential to promote IgE production by B cells [104]. …”
Section: Interaction With Other Cell Typesmentioning
confidence: 99%
“…97 These data suggest ILC2 may influence the B cell and/or IgE compartments in allergic disease. 98 ILC2 also coordinate with cells of the innate immune system. Specifically, basophil derived IL-4 is required for ILC2 responses in a mouse model of atopic dermatitis.…”
Section: Ilc2 Mechanisms Of Pathogenesis In Allergic Diseasementioning
confidence: 99%
“…A recent study provides evidence that ILC2s can contribute to the production of IgE by B cells . That study showed that upon stimulation with IL‐25 or IL‐33, human peripheral ILC2s can enhance IgE production from autologous B cells through expression of CD154 and IL‐4 production in vitro . The functional significance of ILC2s for IgE production by B cells in allergic and asthmatic patients is unknown.…”
Section: Role Of Ilc2s In Disease Pathogenesismentioning
confidence: 99%